Efektivitas Video Edukasi dalam meningkatkan pengetahuan tentang anemia pada remaja di SMP Plus At-Thoiba Pekanbaru - Tri Muhammad Akbar; Eva Mayasari; Rika Mianna; Jufenti Ade Fitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is a public health problem widely experienced by adolescents, particularly in developing countries, including Indonesia. Low levels of knowledge about anemia contribute to its high prevalence. This study aimed to determine the effectiveness of educational videos in improving knowledge about anemia among adolescents at SMP Plus At-Thoiba Pekanbaru. This research employed a quasi-experimental design with a one-group pretest-posttest approach. The population consisted of all eighth-grade students at SMP Plus At-Thoiba Pekanbaru, totaling 17 respondents, selected through total sampling. The instrument used was an anemia knowledge questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normally distributed data. The results showed an increase in the mean knowledge score from 9.59 before the intervention to 12.41 after the intervention. The Wilcoxon test yielded a p-value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. A total of 94.1% of respondents experienced an increase in knowledge after watching the educational video. The study concludes that educational videos are effective in increasing adolescents’ knowledge about anemia. This medium can serve as an appropriate alternative in school health promotion programs to prevent anemia among adolescents.